Telemedicine Supported by Data Warehouse Architecture - Mohd Khanapi, Abd Ghani; Mustafa Musa, Jaber; Suryana, Nanna (2014)
Telemedicine is the new way of delivering health services to patients and can be defined as the provision of medical services by using information technology and communication systems. Moreover, it emphasizes the interaction and collaboration with the increase of sharing information and knowledge between healthcare provider and patient. Healthcare information systems contain large volumes of information that include demographic and medical history of patients such as medication, lab test results, radiology information and procedures that are constantly growing. Thus, the need of complete medical data which supports video, audio and images has to be accomplished before implementing the telemedicine system. The aim of this research is to propose an integrated telemedicine framework supported by data warehouse technique. The proposed framework is evaluated using test case technique and the result showed that data warehouse provide important elements of information to telemedicine system especially during consultation